2017
DOI: 10.1016/j.pediatrneurol.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Seizures in Preterm Neonates: A Multicenter Observational Cohort Study

Abstract: BACKGROUND The purpose of this study was to characterize seizures among preterm neonates enrolled in the Neonatal Seizure Registry, a prospective cohort of consecutive neonates with seizures at seven pediatric centers that follow the American Clinical Neurophysiology Society’s neonatal electroencephalography monitoring guideline. STUDY DESIGN Of 611 enrolled neonates with seizures, 92 (15%) were born preterm. Seizure characteristics were evaluated by gestational age at birth for extremely preterm (<28 weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 23 publications
5
78
0
4
Order By: Relevance
“…Neonates from the initial NSR cohort were previously reported. 2,3,5 Neonates were included if they received a loading dose of an ASM and adequate documentation regarding response to the loading dose was available. Neonates with events that were determined not to be seizures based on history, semiology, or cEEG were not enrolled.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neonates from the initial NSR cohort were previously reported. 2,3,5 Neonates were included if they received a loading dose of an ASM and adequate documentation regarding response to the loading dose was available. Neonates with events that were determined not to be seizures based on history, semiology, or cEEG were not enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…1 Little is known about additional characteristics associated with initial treatment failure, although we previously showed that preterm and term neonates were equally likely to have persistent seizures after a loading dose of phenobarbital 2 and there was no difference in treatment response to initial doses of phenobarbital, phenytoin, or levetiracetam as the first-line ASM. In the 1999 clinical trial of phenobarbital versus phenytoin, seizures recurred in >50% of neonates following the first loading dose of either medication, and neonates with higher seizure burden were less likely to respond.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current consensus guidelines 13 aim to balance the need to identify seizures in critically ill neonates with the substantial personnel and equipment resources required to support cEEG, 14 but are based on limited neonatal data. 26,27 In addition, younger age 28,29 and EEG background abnormalities 22,[30][31][32][33] are associated with increased seizure incidence; however, the impact of early EEG features on the time course of seizure presentation in high-risk neonates is unknown. [15][16][17][18][19][20] Delayed seizure onset beyond 24 hours has been reported in acute neonatal encephalopathy [21][22][23][24][25] and congenital cardiac disease cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] Delayed seizure onset beyond 24 hours has been reported in acute neonatal encephalopathy [21][22][23][24][25] and congenital cardiac disease cohorts. 26,27 In addition, younger age 28,29 and EEG background abnormalities 22,[30][31][32][33] are associated with increased seizure incidence; however, the impact of early EEG features on the time course of seizure presentation in high-risk neonates is unknown.…”
Section: Introductionmentioning
confidence: 99%